A lignin-based nitrogen-sulfur co-doped carbon quantum dot composite photocatalytic antibacterial film and a preparation method thereof
Patent Information
- Application Number
- CN202611049715.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-17
- Publication Date
- 2026-10-16
AI Technical Summary
[0006]本发明的目的是为解决现有技术中光催化抗菌材料光响应范围窄、载流子分离效率低、抗菌效果有限、掺杂工艺复杂等,提供一种木质素基氮硫共掺杂碳量子点复合光催化抗菌薄膜及其制备方法
[0019] This invention has the following beneficial effects: Using enzymatically hydrolyzed lignin as the carbon source, and treated with a concentrated sulfuric acid-concentrated nitric acid mixed acid system, it simultaneously achieves in-situ co-doping of nitrogen and sulfur elements and oxidative etching of the carbon skeleton, without the need to introduce external organic nitrogen or sulfur sources. In this system, nitrogen doping extends the light absorption edge of carbon dots to the visible light region, while sulfur doping reduces the recombination rate of photogenerated electron-hole pairs. Both work synergistically to promote the generation of hydroxyl radicals and superoxide radicals. The mixed acid etching further increases the specific surface area of carbon dots and optimizes their surface defect sites, thereby improving the dispersion uniformity and long-term stability of carbon dots in cellulose-based films. This invention overcomes the shortcomings of traditional photocatalytic antibacterial materials, such as rapid activity decay and poor cycle stability. Furthermore, using agricultural waste lignin as the carbon source and cellulose as the substrate, it combines resource renewability, ease of preparation, and eco-friendliness, showing broad application prospects in food preservation and antibacterial fields.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] This invention relates to the field of photocatalytic antibacterial technology, specifically to a lignin-based nitrogen-sulfur co-doped carbon quantum dot composite photocatalytic antibacterial film and its preparation method. Background Technology
[0002] Currently, the harm caused by microbial contamination such as bacteria and fungi to public health, food safety, environmental governance, and medical care continues to worsen. Existing antimicrobial systems relying solely on traditional antimicrobial agents have many drawbacks. Current antimicrobial strategies generally use organic bactericides, heavy metal ions, or antibiotics as active ingredients. However, organic bactericides have poor thermal stability and unknown degradation products; heavy metal ions tend to accumulate in organisms and have potential toxicity; and the continued use of antibiotics leads to the frequent emergence of drug-resistant strains.
[0003] Compared to traditional antibacterial agents, CQDs exhibit better biocompatibility and lower biotoxicity, demonstrating significant potential in antibacterial and antiviral applications. Some CQDs retain antibacterial activity even under photoexcitation-free conditions, adsorbing onto the cell walls of bacteria or fungi through diffusion and electrostatic interactions, leading to cytoplasmic leakage and ultimately inducing apoptosis. Throughout this process, CQDs maintain excellent biocompatibility and are non-toxic to normal cells.
[0004] Researchers have prepared p-doped carbon quantum dots (CQDs) using m-aminophenol and phosphate as precursors. These CQDs exhibited significant antibacterial activity against *Escherichia coli* and *Staphylococcus aureus*, with minimum inhibitory concentrations (MICs) of 1.23 mg / ml and 1.44 mg / ml, respectively. Treatment with p-doped CQDs resulted in significant morphological disruption of *E. coli* cells and irregular morphology of *S. aureus* cells. Furthermore, CQDs show considerable clinical potential in wound healing. On one hand, CQDs, with their surface defects and unpaired electrons, can effectively scavenge free radicals, protecting wounds from oxidative stress and thus promoting healing. On the other hand, the positively charged surface of CQDs allows them to bind to negatively charged bacterial membranes via electrostatic interactions, disrupting the membrane structure and leading to bacterial death. This characteristic endows them with excellent antibacterial properties, thereby reducing the inflammatory response caused by infection. In addition, mouse experiments showed that spraying CQDs onto wounds effectively promoted healing without significant side effects. Therefore, carbon quantum dots hold great promise for applications in the antibacterial field.
[0005] Existing carbon quantum dot antibacterial materials mostly employ single or double doping with organic nitrogen / sulfur sources (such as urea and thiourea). However, this strategy suffers from low doping efficiency and easy recombination of photogenerated carriers, resulting in limited improvement in antibacterial performance. Furthermore, most studies have not fully utilized the aromatic structural advantages of lignin in biomass carbon sources, and the intrinsic mechanism of nitrogen-sulfur co-doping synergistically enhancing photocatalytic antibacterial performance lacks a systematic explanation. Summary of the Invention
[0006] The purpose of this invention is to address the shortcomings of existing photocatalytic antibacterial materials, such as narrow photoresponse range, low carrier separation efficiency, limited antibacterial effect, and complex doping process, by providing a lignin-based nitrogen-sulfur co-doped carbon quantum dot composite photocatalytic antibacterial film and its preparation method.
[0007] To address the shortcomings of the aforementioned technical problems, the present invention employs the following technical solution: using enzymatically hydrolyzed lignin as the carbon source and a mixed acid system composed of concentrated sulfuric acid and concentrated nitric acid as the sulfur and nitrogen sources, lignin-based nitrogen-sulfur co-doped carbon quantum dots are synthesized via hydrothermal reaction; subsequently, the obtained carbon quantum dots are blended with cellulose acetate and polyethylene glycol to form a film solution, and then a composite photocatalytic antibacterial film is prepared via a casting process.
[0008] As a further optimization of the preparation method of the lignin-based nitrogen-sulfur co-doped carbon quantum dot composite photocatalytic antibacterial film of the present invention: the synthesis of lignin-based nitrogen-sulfur co-doped carbon quantum dots includes the following steps.
[0009] S1: Weigh the enzymatically hydrolyzed lignin, add concentrated sulfuric acid and concentrated nitric acid, mix evenly, then dilute with deionized water, and disperse evenly by ultrasonication to prepare a carbon quantum dot precursor solution; S2: The obtained carbon quantum dot precursor solution is transferred to a hydrothermal reactor, sealed, and then subjected to a hydrothermal reaction. S3: Cool the product obtained from the hydrothermal reaction to room temperature naturally, adjust the pH of the solution, centrifuge, take the supernatant, add NaBH4, and adjust the pH again; S4: Transfer the obtained solution to a dialysis bag and dialyze it with deionized water. Change the dialysis water regularly and collect the liquid remaining in the dialysis bag to obtain a nitrogen-sulfur co-doped carbon quantum dot solution.
[0010] As a further optimization of the preparation method of the lignin-based nitrogen-sulfur co-doped carbon quantum dot composite photocatalytic antibacterial film of the present invention: in the precursor solution of step S1, the mass percentage of enzymatically hydrolyzed lignin is 1%~10%.
[0011] As a further optimization of the preparation method of the lignin-based nitrogen-sulfur co-doped carbon quantum dot composite photocatalytic antibacterial film of the present invention: the volume ratio of concentrated sulfuric acid to concentrated nitric acid in step S1 is 3:0~3:3.
[0012] As a further optimization of the preparation method of the lignin-based nitrogen-sulfur co-doped carbon quantum dot composite photocatalytic antibacterial film of the present invention: the hydrothermal reaction temperature in step S2 is 160~200℃ and the hydrothermal reaction time is 8~16 hours.
[0013] As a further optimization of the preparation method of the lignin-based nitrogen-sulfur co-doped carbon quantum dot composite photocatalytic antibacterial film of the present invention: the pH value is adjusted to 5~9 in both the first and second steps of step S3.
[0014] As a further optimization of the preparation method of the lignin-based nitrogen-sulfur co-doped carbon quantum dot composite photocatalytic antibacterial film of the present invention: the preparation of the composite photocatalytic antibacterial film includes the following steps.
[0015] S1: Dissolve cellulose acetate in 40 mL of glacial acetic acid, disperse it by ultrasonication to obtain a cellulose acetate solution, then add lignin-based nitrogen-sulfur co-doped carbon quantum dots, and disperse them evenly by ultrasonication. S2: Add polyethylene glycol to the ultrasonically treated solution obtained in step S1, stir and mix evenly to obtain a film-forming solution; S3: The obtained film-forming liquid is cast onto a smooth mold, dried under vacuum, and then peeled off to obtain a lignin-based nitrogen-sulfur co-doped carbon quantum dot composite photocatalytic antibacterial film.
[0016] As a further optimization of the preparation method of the lignin-based nitrogen-sulfur co-doped carbon quantum dot composite photocatalytic antibacterial film of the present invention: the mass percentage of cellulose acetate in step S1 is 1%~10%, and the amount of lignin-based nitrogen-sulfur co-doped carbon quantum dot solution is 0~10 mL.
[0017] As a further optimization of the preparation method of the lignin-based nitrogen-sulfur co-doped carbon quantum dot composite photocatalytic antibacterial film of the present invention, in step S2, the molecular weight of polyethylene glycol is 380-420, and the amount of polyethylene glycol used is 1-8 mL.
[0018] The lignin-based nitrogen-sulfur co-doped carbon quantum dot composite photocatalytic antibacterial film prepared by the above method.
[0019] This invention has the following beneficial effects: Using enzymatically hydrolyzed lignin as the carbon source, and treated with a concentrated sulfuric acid-concentrated nitric acid mixed acid system, it simultaneously achieves in-situ co-doping of nitrogen and sulfur elements and oxidative etching of the carbon skeleton, without the need to introduce external organic nitrogen or sulfur sources. In this system, nitrogen doping extends the light absorption edge of carbon dots to the visible light region, while sulfur doping reduces the recombination rate of photogenerated electron-hole pairs. Both work synergistically to promote the generation of hydroxyl radicals and superoxide radicals. The mixed acid etching further increases the specific surface area of carbon dots and optimizes their surface defect sites, thereby improving the dispersion uniformity and long-term stability of carbon dots in cellulose-based films. This invention overcomes the shortcomings of traditional photocatalytic antibacterial materials, such as rapid activity decay and poor cycle stability. Furthermore, using agricultural waste lignin as the carbon source and cellulose as the substrate, it combines resource renewability, ease of preparation, and eco-friendliness, showing broad application prospects in food preservation and antibacterial fields. Attached Figure Description
[0020] Figure 1 This is a BET diagram from Embodiment 1 of the present invention; Figure 2 This is the Fourier transform infrared spectrum of Embodiment 1 of the present invention; Figure 3 This is the ultraviolet-visible diffuse reflectance spectrum of Embodiment 1 of the present invention; Figure 4 This is the photocurrent response diagram of Embodiment 1 of the present invention; Figure 5 This is the impedance diagram of Embodiment 1 of the present invention; Figure 6 These are comparative photographs of colony counts under dark conditions (a) and light conditions (b) in Example 1 of the present invention. Figure 7 This is a comparative diagram of the strawberry preservation experiment in Example 1 of the present invention; Figure 8 This is a comparison chart of the antibacterial rates of Examples 1-6 of the present invention. Detailed Implementation
[0021] To better understand the present invention, the following embodiments further illustrate the content of the present invention, but the content of the present invention is not limited to the following embodiments.
[0022] <Example 1> An N,S-CDs composite photocatalytic antibacterial film was prepared by weighing 1.3 g of enzymatically hydrolyzed lignin, adding 3 mL of concentrated sulfuric acid and 1 mL of concentrated nitric acid, mixing thoroughly, diluting with 26 mL of deionized water, and ultrasonically dispersing for 12 hours to obtain an N,S-CDs precursor solution. The obtained N,S-CDs precursor solution was transferred to a 100 mL hydrothermal reactor, sealed, and hydrothermally reacted at 180℃ for 12 hours. The product obtained from the hydrothermal reaction was naturally cooled to room temperature, the pH of the solution was adjusted to neutral, centrifuged at 7000 r / min for 10 min, and 0.3 g of NaBH4 was added to the supernatant. The pH of the solution was adjusted to neutral again. The above solution was transferred to a dialysis bag with a molecular weight cutoff of 3500, and dialyzed with deionized water for 48 hours. The dialysis water was changed every 12 hours, and the liquid remaining in the dialysis bag was collected to obtain the N,S-CDs solution.
[0023] 3 g of cellulose acetate was dissolved in 40 mL of glacial acetic acid and dispersed by ultrasonication to obtain a cellulose acetate solution. Then, 1 mL of N,S-CDs solution was added and dispersed evenly by ultrasonication. Finally, 4 mL of polyethylene glycol 400 was added and stirred until homogeneous to obtain a film-forming solution. The film-forming solution was then cast onto a smooth 20 cm × 20 cm mold and vacuum-dried at 60 ℃ for 12 h before being peeled off to obtain the N,S-CDs composite photocatalytic antibacterial film.
[0024] <Example 2> The only difference from Example 1 is the volume of the N,S-CDs solution, which is 0 mL.
[0025] <Example 3> The only difference from Example 1 is the volume of the N,S-CDs solution, which is 0.5 mL.
[0026] <Example 4> The only difference from Example 1 is the volume of the N,S-CDs solution, which is 2 mL.
[0027] <Example 5> The only difference from Example 1 is the volume of the N,S-CDs solution, which is 3 mL.
[0028] <Example 6> The only difference from Example 1 is the volume of the N,S-CDs solution, which is 4 mL.
[0029] <Test Example 1> To verify the pore structure characteristics of the N,S-CDs described in this invention, nitrogen adsorption-desorption tests were performed. The results are shown in [Figure number missing]. Figure 1 The adsorption-desorption isotherm of this material belongs to type IV, exhibiting a significant H3-type hysteresis loop in the relative pressure range of P / P0 = 0.7–1.0, indicating the presence of numerous slit-type mesopores formed by the accumulation of nanoparticles. BJH pore size distribution analysis shows that the pore size is mainly concentrated in the 2–10 nm mesopore range, with two characteristic mesopore volume peaks appearing near 3 nm and 8 nm. The differential pore volume decreases significantly after the pore size exceeds 10 nm. These results confirm that the nitrogen-sulfur co-doped carbon quantum dot material prepared in this invention is dominated by a mesoporous structure. This hierarchical stacked mesoporous structure provides sufficient active sites and accelerates the diffusion and transport of reactants and ions, thus demonstrating excellent potential application value in the field of photocatalysis.
[0030] <Test Example 2> To verify the surface functional groups and doping status of the N,S-CDs described in this invention, Fourier transform infrared spectroscopy (FTIR) characterization was performed. The results are shown in [Figure number missing]. Figure 2 2950 cm -1 The absorption peak at 1412 cm⁻¹ is attributed to the vibration of the CH bonds in the lignin skeleton. -1 The characteristic peak at 1061 cm⁻¹ corresponds to the vibrational absorption of the CN bond in the carbon quantum dot, indicating that nitrogen has been successfully incorporated into the carbon quantum dot framework; -1The absorption peak at this point is attributed to the recombination vibration of the CO bond and the sulfonyl S=O bond in the carbon quantum dot, and the appearance of this peak confirms the presence of sulfur functional groups. The above functional group analysis results collectively indicate that nitrogen and sulfur elements have been successfully doped into the carbon quantum dot structure.
[0031] <Test Example 3> To verify the optical properties of the N,S-CDs described in this invention, ultraviolet-visible diffuse reflectance spectroscopy (DRS) characterization was performed. The results are shown in [Figure number missing]. Figure 3 N,S-CDs exhibit a distinct absorption edge around 400 nm, with lignin nitrogen-sulfur co-doped carbon quantum dots showing the highest absorbance, indicating their visible light response characteristics and potential for photocatalytic applications.
[0032] <Test Example 4> To verify the photogenerated carrier separation efficiency of the N,S-CDs described in this invention, instantaneous photocurrent tests were performed. The results are shown below. Figure 4 During the photocurrent test, the photocurrent signal was almost zero when the light-blocking plate blocked the xenon lamp light source; after the light-blocking plate was removed, the sample produced a significant instantaneous photocurrent response. Among them, the photocurrent intensity of N,S-CDs was significantly higher than that of the single-doped sample and the undoped sample, indicating that it has a better photogenerated carrier separation efficiency.
[0033] <Test Example 5> To verify the charge transport characteristics of the N,S-CDs described in this invention, electrochemical impedance spectroscopy (EIS) was performed. The results are shown below. Figure 5 The semi-circular radius of the lignin-based nitrogen-sulfur co-doped carbon quantum dots is significantly smaller than that of the control sample, indicating that they have a lower charge transfer resistance, which is beneficial to the interfacial separation and transport of photogenerated carriers, showing their potential as a highly efficient photocatalyst.
[0034] <Test Example 6> To verify the antibacterial activity of the N,S-CDs described in this invention, *Escherichia coli* was used as a model strain, and an antibacterial experiment was conducted using the plate coating method. The experimental procedure was as follows: 0.1 g of shredded film was weighed and placed in a specially made quartz reactor; the bacterial suspension of *E. coli* was taken and diluted with physiological saline to 10⁻⁶. 6 CFU / mL, take 10 mL and add it to the reactor. Under dark conditions, place at room temperature in the dark for 30 min and then remove it; under light conditions, irradiate at room temperature with a 300 W xenon lamp for 30 min and then remove it. Perform serial dilution plating under sterile conditions, incubate overnight, and then count the colony counts of the experimental group and the control group the next day.
[0035] The results of the antibacterial test are shown below. Figure 6 In figures (a) and (b), the top row represents the control group and the bottom row represents the experimental group. Figure 6(a) Colony growth after plating the bacterial culture at different incubation times under dark conditions. The results show that the number of colonies on the plate decreased with the extension of incubation time, indicating that N,S-CDs themselves have certain antibacterial properties. Figure 6 (b) Colony growth after plating the bacterial culture at different incubation times under light conditions. Compared with the dark group, the number of colonies in the light-illuminated group decreased significantly with increasing incubation time, indicating that N,S-CDs materials exhibit excellent photocatalytic antibacterial properties under light irradiation. These results demonstrate that N,S-CDs possess both intrinsic antibacterial activity and photo-enhanced antibacterial ability, and have the potential to serve as highly efficient antibacterial agents in photocatalytic antibacterial films.
[0036] <Test Example 7> To evaluate the practical application effect of the N,S-CDs antibacterial film of the present invention, a preservation experiment was conducted using strawberries as the preservation target. The results are shown below. Figure 7 During a four-day continuous light exposure period, it was observed that strawberries without film coverage developed bacterial spots first; followed by strawberries covered with PE film and those without added photocatalyst film; while strawberries covered with an antibacterial film containing N,S-CDs photocatalyst showed bacterial spots the latest and had the best preservation effect. The results indicate that the antibacterial film described in this invention has excellent preservation performance, extending the shelf life of strawberries by approximately 3-4 days compared to the control group.
[0037] <Test Example 8> To determine the optimal loading volume of N,S-CDs in the composite photocatalytic antibacterial film, Examples (1-6) investigated the effect of different volumes of N,S-CDs on the antibacterial rate of the composite photocatalytic antibacterial film. The results are shown in […]. Figure 8 The results showed that the composite photocatalytic antibacterial film exhibited significant photocatalytic antibacterial properties after the addition of N,S-CDs, and the optimal carbon dot loading volume was determined.
[0038] The specific embodiments of the present invention have been described above. It should be understood that the present invention is not limited to the specific embodiments described above, and those skilled in the art can make various modifications or variations within the scope of the claims, which do not affect the essence of the present invention.
Claims
1. A method for preparing a lignin-based nitrogen-sulfur co-doped carbon quantum dot composite photocatalytic antibacterial film, characterized in that: Using enzymatically hydrolyzed lignin as the carbon source and a mixed acid system composed of concentrated sulfuric acid and concentrated nitric acid as the sulfur and nitrogen sources, lignin-based nitrogen-sulfur co-doped carbon quantum dots were synthesized via hydrothermal reaction. Subsequently, the obtained carbon quantum dots were mixed with cellulose acetate and polyethylene glycol to prepare a film solution, and then a composite photocatalytic antibacterial film was prepared by casting process.
2. The method for preparing a lignin-based nitrogen-sulfur co-doped carbon quantum dot composite photocatalytic antibacterial film as described in claim 1, characterized in that, Synthesis of lignin-based nitrogen-sulfur co-doped carbon quantum dots Includes the following steps: S1: Weigh the enzymatically hydrolyzed lignin, add concentrated sulfuric acid and concentrated nitric acid, mix evenly, then dilute with deionized water, and disperse evenly by ultrasonication to prepare a carbon quantum dot precursor solution; S2: The obtained carbon quantum dot precursor solution is transferred to a hydrothermal reactor, sealed, and then subjected to a hydrothermal reaction. S3: Cool the product obtained from the hydrothermal reaction to room temperature naturally, adjust the pH of the solution, centrifuge, take the supernatant, add NaBH4, and adjust the pH again; S4: Transfer the obtained solution to a dialysis bag and dialyze it with deionized water. Change the dialysis water regularly and collect the liquid remaining in the dialysis bag to obtain a nitrogen-sulfur co-doped carbon quantum dot solution.
3. The method for preparing a lignin-based nitrogen-sulfur co-doped carbon quantum dot composite photocatalytic antibacterial film as described in claim 2, characterized in that: In the precursor solution of step S1, the mass percentage of enzymatically hydrolyzed lignin is 1% to 10%.
4. The method for preparing a lignin-based nitrogen-sulfur co-doped carbon quantum dot composite photocatalytic antibacterial film as described in claim 2, characterized in that: In step S1, the volume ratio of concentrated sulfuric acid to concentrated nitric acid is 3:0 to 3:
3.
5. The method for preparing a lignin-based nitrogen-sulfur co-doped carbon quantum dot composite photocatalytic antibacterial film as described in claim 2, characterized in that: In step S2, the hydrothermal reaction temperature is 160~200℃ and the hydrothermal reaction time is 8~16 hours.
6. The method for preparing a lignin-based nitrogen-sulfur co-doped carbon quantum dot composite photocatalytic antibacterial film as described in claim 2, characterized in that: In step S3, the pH value is adjusted to 5-9 both times.
7. The method for preparing a lignin-based nitrogen-sulfur co-doped carbon quantum dot composite photocatalytic antibacterial film as described in claim 1, characterized in that, The preparation of the composite photocatalytic antibacterial film includes the following steps: S1: Dissolve cellulose acetate in 40 mL of glacial acetic acid, disperse it by ultrasonication to obtain a cellulose acetate solution, then add a lignin-based nitrogen-sulfur co-doped carbon quantum dot solution and disperse it evenly by ultrasonication. S2: Add polyethylene glycol to the ultrasonically treated solution obtained in step S1, stir and mix evenly to obtain a film-forming solution; S3: The obtained film-forming liquid is cast onto a smooth mold, dried under vacuum, and then peeled off to obtain a lignin-based nitrogen-sulfur co-doped carbon quantum dot composite photocatalytic antibacterial film.
8. The method for preparing a lignin-based nitrogen-sulfur co-doped carbon quantum dot composite photocatalytic antibacterial film as described in claim 7, characterized in that: In step S1, the mass percentage of cellulose acetate is 1% to 10%, and the volume of lignin-based nitrogen-sulfur co-doped carbon quantum dots is 0 to 10 mL.
9. The method for preparing a lignin-based nitrogen-sulfur co-doped carbon quantum dot composite photocatalytic antibacterial film as described in claim 7, characterized in that: In step S2, the molecular weight of polyethylene glycol is 380-420, and the amount of polyethylene glycol used is 1-8 mL.
10. A lignin-based nitrogen-sulfur co-doped carbon quantum dot composite photocatalytic antibacterial film prepared by the method of any one of claims 1 to 9.